Kinerja Auditor Generasi Z Ditinjau dari Karakteristik Individu dan Perilaku Auditor serta Peran Budaya Organisasi - Mia Amelia; Trinandari Prasetya Nugrahanti (ProBisnis : Jurnal Manajemen, 2026)
This study examined the effects of individual characteristics and Generation Z auditors’ behavior on auditor performance, with organizational culture as a moderating variable, at the Main Inspectorate of the General Election Supervisory Agency (Bawaslu). The study was motivated by persistent delays in completing audit reports and the growing dominance of Generation Z auditors within the institution. A quantitative explanatory design was employed, using a survey of 61 Generation Z auditors purposively selected. Data were collected through a structured questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling with SmartPLS 4. The results showed that individual characteristics had a positive and significant effect on auditor performance, and auditor behavior also had a positive and significant effect on performance. Organizational culture had a direct positive effect on performance, but it did not moderate the relationship between individual characteristics and performance or between auditor behavior and performance. These findings indicate that auditor performance in this context was more strongly driven by internal individual factors than by the contingent role of organizational culture.